The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1111/j.1469-1809.1978.tb01901.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of red cell enzymes in Alaskan ethnic groups

Abstract: 1. Gene frequencies of esterase D, glyoxalase I and uridine monophosphate kinase in Alaskan populations were determined. 2. Improved methods for demonstrating phenotypes of glyoxalase I and uridine monophosphate kinase are presented. 3. Rare variants of adenylate kinase (AK1) and diaphorase (DIA) were found. One of the AK1 variants is new. 4. Gene frequencies were notably diverse within major ethnic groups. This variability was consistent with a population structure composed of small groups that were relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

1981
1981
1999
1999

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
1
11
1
Order By: Relevance
“…In addition to the common allele GOT*1, two different electrophoretically identifiable alleles were reported (Chen and Giblett, 1971;Ishimoto and Kuwata, 1974;Teng and others, 1978;Scott and Wright, 1978). However, in this study, distribution of GOT in all the individuals of the nine Taiwan ethnic groups showed the identical type, GOT 1.…”
Section: Monomorphic Locicontrasting
confidence: 46%
“…In addition to the common allele GOT*1, two different electrophoretically identifiable alleles were reported (Chen and Giblett, 1971;Ishimoto and Kuwata, 1974;Teng and others, 1978;Scott and Wright, 1978). However, in this study, distribution of GOT in all the individuals of the nine Taiwan ethnic groups showed the identical type, GOT 1.…”
Section: Monomorphic Locicontrasting
confidence: 46%
“…The gene frequencies at the phenotypic loci that we observed do not differ signif icantly from other reports in the Yupikspeaking Eskimo for ESD [6,7] and ACP, AK, HP, GLO, PGM, and GPT [4. 5, 7], and the blood groups ABO and MN [38].…”
Section: Discussionmentioning
confidence: 34%
“…In the Arctic Investigations Laboratory, stan dard methods were utilized for characterizing the red cell enzymes ESD [26] and GPT [27], UMPK [6]. and the erythrocyte antigens ABO.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of AK*4 is more difficult to interpret. A variant with about the same electrophoretic mobility was observed in very low prevalences in the United Kingdom and Africa (Rapley et al, 1967;Hiernaux, 1976), but also in North American Indians (Athabaskans) and Eskimos (Scott and Wright, 1978). The finding of one Rh negative among the Surui (see footnote, Table 1) also could be due to admixture.…”
Section: Resultsmentioning
confidence: 69%